Inovasi Produk Kerajinan dari Limbah Kulit Jagung sebagai Strategi Pengembangan Green Entrepreneurship dalam Mewujudkan Model Bisnis Berkelanjutan Berbasis Ekonomi Hijau - Alhafidz, Zidan Rizka (Jurnal Ilmu Manajemen dan Bisnis, 2025)
Corn husk waste, which is abundant in agricultural areas, is often discarded or burned, causing environmental problems such as air pollution and soil fertility degradation. This study aims to analyze the development and implementation process of corn husk–based handicraft products as a form of green entrepreneurship that supports the green economy and sustainable development. The research employs a descriptive qualitative approach with a case study method, collecting data through self-reflection, documentation, interviews with consumers, field observations, and literature review. Data were analyzed using descriptive qualitative analysis, SWOT analysis, and business performance analysis with triangulation techniques to ensure data validity. The findings show that corn husk waste can be processed into shopping bags and tissue box holders through a series of stages: collection, cleaning, drying, cutting, weaving, and finishing. The products are sold at prices of IDR 75,000 for shopping bags and IDR 45,000 for tissue holders, marketed both online and offline to local communities with positive consumer responses. The business, which has been running for three months, produces around 20 units per month with fluctuating sales levels but demonstrates promising economic feasibility. The main challenge lies in the weaving process, which requires specific craftsmanship skills. This enterprise provides positive impacts, including reducing agricultural waste, preventing air pollution, creating new economic opportunities, and preserving traditional weaving skills. The study concludes that the development of corn husk–based products represents an effective model of green entrepreneurship that integrates economic, environmental, and social values, contributing to the achievement of sustainable development goals.